Resin composition, temporary fixing material, and method for manufacturing electronic component
A resin composition with an imide skeleton and (meth)acrylic copolymer addresses the issue of gaps and excessive adhesion in temporary fixing materials by enhancing peeling performance during high-temperature treatments, particularly for polyimide surfaces.
Patent Information
- Application Number
- CN202380041819.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-21
- Filing Date
- 2023-09-21
- Publication Date
- 2024-12-17
AI Technical Summary
Conventional temporary fixing materials for electronic components fail to prevent gaps or lifting during high-temperature heat treatments and often result in excessive adhesion or residual adhesive, especially when polyimide is used on the surface.
A resin composition comprising a resin with an imide skeleton in the main chain and a (meth)acrylic copolymer, specifically with a structural unit derived from branched alkyl (meth)acrylate, is used to create a temporary fixing material that suppresses voids and floating during heat treatment and allows easy peeling.
The resin composition effectively prevents gaps and floating during high-temperature processing while ensuring easy peeling, maintaining adhesion without residual adhesive, even on polyimide surfaces.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and also to a temporary fixing material comprising the resin composition and a method for producing an electronic component using the temporary fixing material. Background Art
[0002] When processing electronic components such as semiconductors, in order to facilitate the handling of the electronic components and prevent them from being damaged, the following operations are performed: the electronic components are fixed to a support plate with the aid of a temporary fixing material containing a resin composition, or an adhesive tape made of a temporary fixing material having an adhesive layer containing a resin composition is attached to the electronic components to protect them. For example, in the case of grinding a thick film wafer cut from high-purity single crystal silicon to a predetermined thickness to form a thin film wafer, the thick film wafer is bonded to a support plate with the aid of a temporary fixing material.
[0003] Temporary fixing materials used for electronic components are required to have high adhesion to fix the electronic components as firmly as possible during the processing step, and to be able to be peeled off without damaging the electronic components after the process is completed (hereinafter also referred to as "high adhesion and easy peeling").
[0004] As a means of achieving high adhesion and easy peeling, for example, Patent Document 1 discloses an adhesive sheet using an adhesive having a multifunctional monomer or oligomer having a radiation polymerizable functional group bonded to the side chain or main chain of the polymer. The polymer is cured by ultraviolet irradiation due to the radiation polymerizable functional group, and this is utilized to reduce the adhesive force by irradiating ultraviolet light during peeling, so that peeling can be performed without residual adhesive.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 5-32946 Summary of the invention
[0008] Problems to be solved by the invention
[0009] With the recent improvement in the performance of electronic components, various processes have been performed on electronic components. For example, in the process of forming a metal thin film on the surface of an electronic component by sputtering, a metal thin film with better conductivity can be formed by performing the process while heating at a high temperature.
[0010] However, when electronic components protected by conventional temporary fixing materials are subjected to a heat treatment at high temperature, gaps or lifting may occur between the electronic components and the support to which they are fixed during heating. Also, excessive adhesion may occur, and the adhesive force may not be sufficiently reduced during peeling, or residual adhesive may be generated.
[0011] In particular, in recent years, polyimide has been used in many electronic components as a material with high heat resistance, and the following processes have been started: fixing an adherend having polyimide on the surface to a support body containing inorganic materials such as glass, and performing various processing steps. In the case where the adherend has polyimide on the surface, if a heat treatment is performed at a high temperature, there is a tendency for hyperadhesion to become greater compared to the case where the surface of the adherend is an inorganic material. In such a case, for a temporary fixing material used to protect the adherend, it is required to suppress hyperadhesion with the adherend on the one hand, and on the other hand, it is also required to suppress the generation of gaps and floating between the support body.
[0012] The object of the present invention is to provide a resin composition which can suppress the generation of voids and floating during heat treatment and can be easily peeled off after heat treatment. In addition, the object of the present invention is to provide a temporary fixing material comprising the resin composition and a method for manufacturing an electronic component using the temporary fixing material.
[0013] Means for solving problems
[0014] The present invention 1 relates to a resin composition comprising a resin having an imide skeleton in a repeating unit of a main chain and a (meth)acrylic copolymer.
[0015] The present invention 2 is related with the resin composition of the present invention 1, wherein the (meth)acrylic copolymer has a structural unit derived from a branched alkyl (meth)acrylate.
[0016] The third aspect of the present invention relates to the resin composition of the second aspect of the present invention, wherein, regarding the (meth)acrylic copolymer, the content ratio of the structural unit derived from the branched alkyl (meth)acrylate in the (meth)acrylic copolymer is 20 mol % or more and 80 mol % or less.
[0017] The present invention 4 relates to the resin composition of the present invention 1, 2 or 3, wherein the (meth)acrylic copolymer comprises a structural unit derived from an alkyl (meth)acrylate having an alkyl group having 2 to 7 carbon atoms and a structural unit derived from an alkyl (meth)acrylate having an alkyl group having 8 to 8 carbon atoms, and the content ratio of the structural unit derived from the alkyl (meth)acrylate having an alkyl group having 2 to 7 carbon atoms in the (meth)acrylic copolymer is 20 mol% to 80 mol%.
[0018] Invention 5 relates to the resin composition of invention 1, 2, 3 or 4, wherein the (meth)acrylic copolymer does not have a reactive functional group having a carbon-carbon double bond.
[0019] The present invention 6 is related with the resin composition of the present invention 1, 2, 3, 4 or 5, wherein the molecular weight of the (meth)acrylic copolymer is 2000 or more and 20,000 or less.
[0020] The present invention 7 relates to the resin composition of the present invention 1, 2, 3, 4, 5 or 6, wherein the glass transition temperature of the (meth)acrylic copolymer is -70°C or higher and -5°C or lower.
[0021] Invention 8 relates to the resin composition of invention 1, 2, 3, 4, 5, 6 or 7, wherein the resin having an imide skeleton in the repeating unit of the main chain includes a resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain.
[0022] The present invention 9 is directed to the resin composition of the present invention 8, wherein the resin having no maleimide group and having an imide skeleton in a repeating unit of the main chain has an aliphatic group derived from a dimer diamine.
[0023] Invention 10 relates to the resin composition of invention 1, 2, 3, 4, 5, 6, 7, 8 or 9, which is thermosetting or photocurable.
[0024] Invention 11 relates to the resin composition of invention 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, which contains a compound having a maleimide group.
[0025] The present invention 12 relates to the resin composition of the present invention 11, wherein the compound having a maleimide group is a bismaleimide compound or a resin having a maleimide group and having an imide skeleton in a repeating unit of the main chain.
[0026] The present invention 13 relates to the resin composition of the present invention 12, which contains a resin having a structural unit represented by the following formula (1) and having a functional group having a maleimide group at at least any position of the terminal and the side chain as the resin having a maleimide group and having an imide skeleton in the repeating unit of the main chain.
[0027] Invention 14 relates to the resin composition of invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, which further comprises a polyfunctional monomer or a polyfunctional oligomer, wherein the polyfunctional monomer or the polyfunctional oligomer has two or more reactive functional groups having carbon-carbon double bonds in the molecule, and the molecular weight of the polyfunctional monomer or the polyfunctional oligomer is 5000 or less.
[0028] Invention 15 relates to the resin composition of Invention 14, wherein the content of the (meth)acrylic copolymer is 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the total of the resin having an imide skeleton in the repeating unit of the main chain and the polyfunctional monomer or polyfunctional oligomer.
[0029] Invention 16 relates to the resin composition of invention 1, 2, 3, 4, 5, 6, 7, 8 or 9, which is non-curable.
[0030] Invention 17 relates to the resin composition of invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16, wherein the 10% weight reduction temperature of the above-mentioned resin composition is above 200°C.
[0031] Invention 18 relates to a temporary fixing material comprising the resin composition of invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17.
[0032] Invention 19 relates to a temporary fixing material having an adhesive layer comprising the resin composition of invention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17.
[0033] Invention 20 relates to the temporary fixing material of invention 19, which is in a tape shape.
[0034] Invention 21 relates to the temporary fixing material of invention 18, 19 or 20, wherein the initial adhesive force of the temporary fixing material to polyimide at 25°C is 0.1 N / inch or more and 1.5 N / inch or less.
[0035] The present invention 22 relates to a method for manufacturing an electronic component, which includes: a temporary fixing process of temporarily fixing the electronic component to the temporary fixing material of the present invention 18, 19, 20 or 21; a heat treatment process of heat treating the above-mentioned electronic component; and a peeling process of peeling the above-mentioned electronic component from the above-mentioned temporary fixing material.
[0036] Invention 23 relates to the method for manufacturing an electronic component of Invention 22, which includes a curing step of curing the temporary fixing material between the temporary fixing step and the heat treatment step.
[0037] [Chemical formula 1]
[0038]
[0039] In formula (1), P 1 represents an aromatic group, Q 1It represents a substituted or unsubstituted straight-chain, branched or cyclic aliphatic group.
[0040] Hereinafter, the present invention will be described in detail.
[0041] The present inventors have studied a proposal to use a resin composition containing a resin having an imide skeleton in a repeating unit of the main chain and a (meth)acrylic copolymer as a resin composition used as a temporary fixing agent. As a result, they found that a resin composition capable of suppressing the generation of voids and floating during heat treatment and being easily peelable after heat treatment can be obtained, thereby completing the present invention.
[0042] The resin composition of the present invention contains a (meth)acrylic acid copolymer. The (meth)acrylic acid copolymer has a function as a surface modifier. By using the (meth)acrylic acid copolymer in combination with a resin having an imide skeleton in a repeating unit of the main chain described later, the resin composition of the present invention can suppress the generation of voids and floating during heat treatment and can be easily peeled off after heat treatment.
[0043] In addition, in this specification, the said "(meth)acrylic acid" means acrylic acid or methacrylic acid.
[0044] The (meth)acrylic acid copolymer preferably has a structural unit derived from a branched (meth)acrylic acid alkyl ester. When the (meth)acrylic acid copolymer has the structural unit derived from a branched (meth)acrylic acid alkyl ester, the dispersibility in the resin composition is improved. In addition, since the partial distribution rate to the surface is improved, the releasability of the temporary fixing material containing the obtained resin composition is further improved.
[0045] It should be noted that, in the present specification, the above-mentioned “(meth)acrylate” means acrylate or methacrylate.
[0046] Examples of the branched alkyl (meth)acrylate include tert-butyl (meth)acrylate, isobutyl (meth)acrylate, isoamyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, isostearyl (meth)acrylate, isooctyl (meth)acrylate, and isoundecyl (meth)acrylate.
[0047] The preferred lower limit of the content ratio of the structural unit derived from the branched (meth) alkyl acrylate in the (meth) acrylic copolymer is 20 mol%, and the preferred upper limit is 80 mol%. By making the content ratio of the structural unit derived from the branched (meth) alkyl acrylate more than 20 mol% and less than 80 mol%, the surface-biased distribution rate in the resin composition can be further improved. As a result, the peelability of the temporary fixing material containing the obtained resin composition becomes more excellent. The more preferred lower limit of the content ratio of the structural unit derived from the branched (meth) alkyl acrylate is 30 mol%, and the more preferred upper limit is 70 mol%.
[0048] The (meth)acrylic copolymer may have a structural unit derived from the branched alkyl (meth)acrylate and a structural unit derived from a linear alkyl (meth)acrylate.
[0049] Examples of the linear alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, n-decyl (meth)acrylate, and n-undecyl (meth)acrylate.
[0050] The (meth)acrylic copolymer preferably has a structural unit derived from an alkyl (meth)acrylate having an alkyl group with 2 to 7 carbon atoms and a structural unit derived from an alkyl (meth)acrylate having an alkyl group with 8 to 8 carbon atoms. When the (meth)acrylic copolymer has the structural unit derived from an alkyl (meth)acrylate having an alkyl group with 2 to 7 carbon atoms and the structural unit derived from an alkyl (meth)acrylate having an alkyl group with 8 to 8 carbon atoms, the dispersibility and surface distribution in the obtained resin composition are further improved.
[0051] The structural unit derived from the branched (meth) alkyl ester preferably has 8 or more carbon atoms. By making the structural unit derived from the branched (meth) alkyl ester have 8 or more carbon atoms, the surface-biased distribution rate in the resin composition can be further increased. As a result, the releasability of the temporary fixing material containing the obtained resin composition becomes more excellent. The structural unit derived from the branched (meth) alkyl ester preferably has 20 or less carbon atoms, preferably 15 or less, preferably 10 or less, and particularly preferably 8.
[0052] The structural unit derived from the linear (meth) alkyl ester preferably has a carbon number of 2 or more and 7 or less. By making the structural unit derived from the linear (meth) alkyl ester have a carbon number of 2 or more and 7 or less, the surface-biased distribution rate in the resin composition can be further improved. As a result, the releasability of the temporary fixing material containing the obtained resin composition becomes more excellent. The structural unit derived from the linear (meth) alkyl ester preferably has a carbon number of 3 or more and 6 or less, and particularly preferably 4.
[0053] Among the alkyl (meth)acrylates having an alkyl group having 2 to 7 carbon atoms, examples of the branched alkyl (meth)acrylate include tert-butyl (meth)acrylate, isobutyl (meth)acrylate, and isopentyl (meth)acrylate.
[0054] Among the above-mentioned alkyl (meth)acrylates having an alkyl group having 2 to 7 carbon atoms, examples of the above-mentioned linear alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, and n-heptyl (meth)acrylate. Among them, in the resin composition of the present invention, n-butyl (meth)acrylate is preferred from the viewpoint of being easily distributed on the surface and improving the releasability.
[0055] Among the alkyl (meth)acrylates having an alkyl group with 8 or more carbon atoms, examples of the branched alkyl (meth)acrylates include 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, isostearyl (meth)acrylate, and isoundecyl (meth)acrylate.
[0056] Among the above-mentioned alkyl (meth)acrylates having an alkyl group having 8 or more carbon atoms, examples of the above-mentioned linear alkyl (meth)acrylates include n-octyl (meth)acrylate, n-nonyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, n-decyl (meth)acrylate, and n-undecyl (meth)acrylate.
[0057] Among them, in the resin composition of the present invention, 2-ethylhexyl (meth)acrylate is preferred from the viewpoint of being easily distributed preferentially on the surface and improving the releasability.
[0058] When the (meth)acrylic copolymer has the structural unit derived from the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 2 or more and 7 or less and the structural unit derived from the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 8 or more, the preferred lower limit of the content of the structural unit derived from the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 2 or more and 7 or less in the (meth)acrylic copolymer is 20 mol% or more, and the preferred upper limit is 80 mol%. By setting the content of the structural unit derived from the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 2 or more and 7 or less to 20 mol% or more, the dispersibility and surface distribution of the obtained resin composition are further improved. By setting the content of the structural unit derived from the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 2 or more and 7 or less to 80 mol% or less, the heat resistance of the obtained resin composition is further improved. The more preferred lower limit of the content of the structural unit derived from the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 2 or more and 7 or less is 30 mol%, and the more preferred upper limit is 70 mol%.
[0059] The (meth)acrylic copolymer preferably further has a structural unit derived from a monomer containing a polar functional group. When the (meth)acrylic copolymer has a structural unit derived from a monomer containing a polar functional group, the obtained resin composition has excellent heat resistance.
[0060] Examples of the structural unit derived from the polar functional group-containing monomer include a structural unit derived from a hydroxyl group-containing monomer, a structural unit derived from a carboxyl group-containing monomer, a structural unit derived from an epoxy group-containing monomer, a structural unit derived from an isocyanate group-containing monomer, a structural unit derived from an amino group-containing monomer, etc. Among them, from the viewpoint of further improving heat resistance, the (meth)acrylic copolymer preferably has a structural unit derived from a hydroxyl group-containing monomer and an epoxy group-containing monomer.
[0061] Examples of the hydroxyl group-containing monomer include 4-hydroxybutyl (meth)acrylate and 2-hydroxyethyl (meth)acrylate.
[0062] Examples of the carboxyl group-containing monomer include acrylic acid and methacrylic acid.
[0063] As said epoxy group-containing monomer, glycidyl (meth)acrylate etc. are mentioned, for example.
[0064] Examples of the isocyanate group-containing monomer include 2-isocyanatoethyl (meth)acrylate and the like.
[0065] As said amino group-containing monomer, 2-aminoethyl (meth)acrylate etc. are mentioned, for example.
[0066] The above-mentioned polar functional group-containing monomers may be used alone or in combination of two or more.
[0067] The preferred lower limit of the total content ratio of the structural units derived from the monomers containing polar functional groups in the (meth) acrylic copolymer is 0.5 mol%, and the preferred upper limit is 30 mol%. By making the total content ratio of the structural units derived from the monomers containing polar functional groups 0.5 mol% or more, the heat resistance of the obtained resin composition becomes excellent. By making the total content ratio of the structural units derived from the monomers containing polar functional groups 30 mol% or less, the peelability after heating becomes excellent. The more preferred lower limit of the total content ratio of the structural units derived from the monomers containing polar functional groups is 1 mol%, the more preferred upper limit is 20 mol%, the further preferred lower limit is 5 mol%, and the further preferred upper limit is 15 mol%.
[0068] The (meth)acrylic copolymer preferably does not have a reactive functional group having a carbon-carbon double bond in the resin composition, from the viewpoint of being easily distributed on the surface and improving the releasability of the obtained temporary fixing material.
[0069] The preferred lower limit of the molecular weight of the (meth) acrylic copolymer is 2000, and the preferred upper limit is 50,000. By setting the molecular weight of the (meth) acrylic copolymer to 2000 or more, the heat resistance of the obtained resin composition becomes more excellent. By setting the molecular weight of the (meth) acrylic copolymer to 50,000 or less, the dispersibility and surface distribution in the obtained resin composition become more excellent. As a result, the releasability of the temporary fixing material containing the obtained resin composition becomes more excellent. The more preferred lower limit of the molecular weight of the (meth) acrylic copolymer is 5000, the further preferred lower limit is 6000, the more preferred upper limit is 20,000, the further preferred upper limit is 15,000, and the further preferred upper limit is 10,000.
[0070] It should be noted that in this specification, the above-mentioned "molecular weight" is a molecular weight obtained from a structural formula for a compound with a specified molecular structure, and a weight-average molecular weight is used to represent a compound with a wide distribution of polymerization degree and a compound with an unspecified modification site. The above-mentioned weight-average molecular weight is measured in the form of a polystyrene-converted molecular weight by gel permeation chromatography (GPC). Specifically, for example, the Acquity APC system (manufactured by Waters) can be used to measure under the conditions of a mobile phase of THF, a flow rate of 1.0 mL / min, a column temperature of 40°C, a sample concentration of 0.2 mol%, and an RI·PDA detector. As the above-mentioned column, HR-MB-M 6.0×150 mm (manufactured by Waters) and the like can be used.
[0071] The preferred lower limit of the glass transition temperature of the (meth)acrylic copolymer is -70°C, and the preferred upper limit is -5°C. By setting the glass transition temperature of the (meth)acrylic copolymer to be within this range, the dispersibility and surface distribution in the obtained resin composition become more excellent. As a result, the releasability of the temporary fixing material containing the obtained resin composition becomes more excellent. The more preferred lower limit of the glass transition temperature of the (meth)acrylic copolymer is -65°C, the further preferred lower limit is -60°C, the more preferred upper limit is -10°C, the further preferred upper limit is -20°C, and the further preferred upper limit is -30°C.
[0072] It should be noted that in this specification, the above-mentioned "glass transition temperature" refers to: the temperature at which the maximum value caused by microscopic Brownian motion appears in the maximum value of the loss tangent (tanδ) obtained by dynamic viscoelasticity measurement. The above-mentioned glass transition temperature can be measured by a conventionally known method using a dynamic viscoelasticity measuring device. In addition, the glass transition temperature (absolute temperature) of the above-mentioned (meth)acrylic copolymer can also be obtained as follows: for each monomer component constituting the (meth)acrylic copolymer, the value obtained by dividing the content ratio by the glass transition temperature is calculated ((monomer component content ratio (mol %)) / (monomer component glass transition temperature (K))), and the reciprocal (Japanese: inverse number) of the value obtained by summing up the values of all monomer components constituting the (meth)acrylic copolymer is calculated.
[0073] The preferred lower limit of the hydroxyl value of the (meth)acrylic copolymer is 1 mgKOH / g, and the preferred upper limit is 100 mgKOH / g. By setting the hydroxyl value of the (meth)acrylic copolymer to 1 mgKOH / g or more, the heat resistance of the obtained resin composition becomes excellent. By setting the hydroxyl value of the (meth)acrylic copolymer to 100 mgKOH / g or less, the peelability of the obtained resin composition after heating becomes excellent. The more preferred lower limit of the hydroxyl value of the (meth)acrylic copolymer is 5 mgKOH / g, the more preferred upper limit is 50 mgKOH / g, the further preferred lower limit is 10 mgKOH / g, and the further preferred upper limit is 30 mgKOH / g.
[0074] The hydroxyl value of the (meth)acrylic acid-based copolymer can be measured, for example, by a potentiometric titration method in accordance with JIS K0070:1992.
[0075] The preferred lower limit of the content of the (meth) acrylic copolymer is 0.1 parts by mass, and the preferred upper limit is 20 parts by mass, relative to 100 parts by mass of the resin having an imide skeleton in the repeating unit of the main chain described later (when the resin composition contains a polyfunctional monomer or polyfunctional oligomer described later, it is 100 parts by mass of the total of the resin having an imide skeleton in the repeating unit of the main chain and the polyfunctional monomer or polyfunctional oligomer). By making the content of the (meth) acrylic copolymer within this range, the temporary fixing material using the obtained resin composition reduces the contamination of the adherend and becomes more excellent in peelability. The more preferred lower limit of the content of the (meth) acrylic copolymer is 0.2 parts by mass, and the more preferred upper limit is 15 parts by mass.
[0076] The resin composition of the present invention contains a resin having an imide skeleton in a repeating unit of the main chain.
[0077] The resin having an imide skeleton in the repeating unit of the main chain has an imide skeleton, so it has extremely excellent heat resistance, and the main chain is not easily decomposed even when subjected to heat treatment at high temperature. Therefore, by containing the resin having an imide skeleton in the repeating unit of the main chain, the temporary fixing material using the obtained resin composition can suppress the generation of gaps and floating between the support during heat treatment at high temperature, and can also prevent excessive adhesion to the adherend or residual adhesive from being generated when peeling from the adherend.
[0078] The resin having an imide skeleton in the repeating unit of the main chain preferably has a structural unit represented by the above formula (1).
[0079] In the above formula (1), P 1Preferably, the aromatic group has 5 to 50 carbon atoms. 1 The aromatic group has a carbon number of 5 or more and 50 or less, so that the heat resistance of the obtained resin composition becomes more excellent. That is, the temporary fixing material using the obtained resin composition can further suppress the generation of gaps and floating between the support body during the heat treatment at high temperature, and can further prevent the adhesion to the adherend from being excessive or the generation of residual adhesive when peeling from the adherend.
[0080] In the above formula (1), Q 1 It is preferably a substituted or unsubstituted linear, branched or cyclic aliphatic group having 2 to 100 carbon atoms. 1 The present invention relates to a substituted or unsubstituted linear, branched or cyclic aliphatic group having 2 to 100 carbon atoms, so that the light transmittance of the temporary fixing material using the obtained resin composition becomes better. In addition, the temporary fixing material using the obtained resin composition has better flexibility, can exhibit high followability to the adherend with uneven surfaces, and can be more easily peeled off when peeling off.
[0081] In addition, the above Q 1 Preferably, the aliphatic group is derived from a diamine compound. From the viewpoint of light transmittance, flexibility, and compatibility of the resin having an imide skeleton in the repeating unit of the main chain with solvents and other components, the Q 1 Preferred are aliphatic groups derived from dimer diamines.
[0082] The dimer diamine is a diamine compound obtained by reducing and aminating a cyclic or acyclic dimer acid obtained as a dimer of an unsaturated fatty acid, and examples thereof include linear, monocyclic, and polycyclic dimer diamines. The dimer diamine may contain a carbon-carbon double bond or may be a hydride to which hydrogen is added.
[0083] The aliphatic group derived from the dimer diamine is preferably at least one group selected from the group represented by the following formula (2-1), the group represented by the following formula (2-2), the group represented by the following formula (2-3), and the group represented by the following formula (2-4). Among them, the group represented by the following formula (2-2) is more preferred.
[0084] [Chemical formula 2]
[0085]
[0086] In formulas (2-1) to (2-4), R 1 ~R 16Each independently represents a linear or branched hydrocarbon group, and * represents a bond. The bond * is bonded to N in the above formula (1).
[0087] In the above general formulas (2-1) to (2-4), R 1 ~R 16 The hydrocarbon group shown can be a saturated hydrocarbon group or an unsaturated hydrocarbon group. 1 With R 2 , R 3 With R 4 , R 5 With R 6 , R 7 With R 8 , R 9 With R 10 , R 11 With R 12 , R 13 With R 14 , and R 15 With R 16 The total number of carbon atoms is preferably 7 or more and 50 or less. By making the total number of carbon atoms in the above range, the light transmittance and flexibility of the obtained resin composition become better, and the compatibility of the resin having an imide skeleton in the repeating unit of the main chain with the solvent and other components also becomes better. The total number of carbon atoms is more preferably 9 or more, more preferably 12 or more, and more preferably 14 or more. The total number of carbon atoms is more preferably 35 or less, more preferably 25 or less, and more preferably 18 or less.
[0088] In the group represented by the above formula (2-1), the group represented by the above formula (2-2), the group represented by the above formula (2-3), and the group represented by the above formula (2-4), optical isomerism is not particularly limited, and any optical isomerism is included.
[0089] The resin having an imide skeleton in a main chain repeating unit preferably includes a resin having no maleimide group and having an imide skeleton in a main chain repeating unit, and more preferably includes a resin having no reactive functional group having a carbon-carbon double bond and having an imide skeleton in a main chain repeating unit.
[0090] The weight average molecular weight of the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain is preferably 10,000 or more and 2,000,000 or less. By making the weight average molecular weight of the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain more than 10,000, the heat resistance of the obtained resin composition becomes more excellent. That is, the temporary fixing material using the obtained resin composition can further suppress the generation of gaps and floating between the support during the heating treatment at high temperature, and can further prevent the adhesion hyperactivity caused to the adherend or the generation of residual glue when peeling from the adherend. By making the weight average molecular weight of the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain less than 2,000,000, the compatibility of the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain with solvents and other components becomes more excellent. The weight average molecular weight of the resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain is more preferably 30,000 in the lower limit, 1,000,000 in the upper limit, 40,000 in the lower limit, 300,000 in the upper limit, and 50,000 in the lower limit.
[0091] Specific examples of the resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain include a resin having a structural unit represented by the above formula (1) and having functional groups having no maleimide group at both terminals.
[0092] The resin having the structural unit represented by the above formula (1) and having functional groups having no maleimide group at both ends may have the structural unit represented by the following formula (3).
[0093] [Chemical formula 3]
[0094]
[0095] In formula (3), P 2 represents an aromatic group, Q 2 It represents a substituted or unsubstituted group having an aromatic structure.
[0096] In the above formula (3), P 2 Preferably, the aromatic group has 5 to 50 carbon atoms. 2 The aromatic group has a carbon number of 5 or more and 50 or less, so that the heat resistance of the obtained resin composition becomes more excellent. That is, the temporary fixing material using the obtained resin composition can further suppress the generation of gaps and floating between the support body during the heat treatment at high temperature, and can further prevent the adhesion to the adherend from being excessive or the generation of residual adhesive when peeling from the adherend.
[0097] In the above formula (3), Q 2 It is preferably a substituted or unsubstituted group having an aromatic structure and having 5 to 50 carbon atoms. 2 The substituted or unsubstituted group having an aromatic structure and having a carbon number of 5 or more and 50 or less can further improve the heat resistance of the obtained resin composition. That is, the temporary fixing material using the obtained resin composition can further suppress the generation of gaps and floating between the support and the support during the heat treatment at high temperature, and can further prevent the adhesion to the adherend from being excessive or the generation of residual adhesive when peeling from the adherend.
[0098] Examples of the functional group not having a maleimide group include aliphatic groups, alicyclic groups, aromatic groups, acid anhydride groups, amino groups, etc. Specifically, examples include unreacted single-terminal constituent groups of acid anhydrides and diamine compounds that are raw materials for the resin not having a maleimide group and having an imide skeleton in the repeating unit of the main chain.
[0099] In the resin having the structural unit represented by the above formula (1) and having functional groups not having a maleimide group at both terminals, the functional groups not having a maleimide group at both terminals may be the same or different.
[0100] The content ratio of the structural unit represented by the above formula (1) in the resin having the structural unit represented by the above formula (1) and having functional groups having no maleimide group at both ends is preferably 30 mol % or more, more preferably 50 mol % or more, and is preferably 90 mol % or less, more preferably 80 mol % or less.
[0101] When the resin having the structural unit represented by the above formula (1) and having a functional group having no carbon-carbon double bond at both ends has the structural unit represented by the above formula (3), the content ratio of the structural unit represented by the above formula (3) is preferably 5 mol% or more, more preferably 10 mol% or more, further preferably 20 mol% or more, and is preferably 50 mol% or less, more preferably 30 mol% or less.
[0102] By setting the content ratio of each structural unit in the structural unit represented by the above formula (1) and the structural unit represented by the above formula (3) to be within the above range, the temporary fixing material using the obtained resin composition can further suppress the generation of voids and floating between the support and the adhesive during heat treatment at high temperature, and can also be more easily peeled off from the adherend.
[0103] The structural unit represented by the above formula (1) and the structural unit represented by the above formula (3) may have a block structure including block components in which the structural units are continuously arranged, or may have a random structure in which the structural units are randomly arranged.
[0104] Examples of a method for producing the resin having no maleimide group and having an imide skeleton in a repeating unit of the main chain include a method of reacting a diamine compound with an aromatic acid anhydride.
[0105] As the diamine compound, any of an aliphatic diamine compound and an aromatic diamine compound can be used.
[0106] By using an aliphatic diamine compound as the diamine compound, the light transmittance of the obtained resin composition becomes better. In addition, the flexibility of the obtained resin composition becomes better, and the temporary fixing material using the obtained resin composition can have high followability to the adherend with unevenness and can be more easily peeled off when peeling off.
[0107] Moreover, by using an aromatic diamine compound as the diamine compound, the heat resistance of the obtained resin composition becomes more excellent.
[0108] The above-mentioned diamine compounds may be used alone or in combination of two or more.
[0109] Examples of the aliphatic diamine compound include 1,10-diaminodecane, 1,12-diaminododecane, dimer diamine, 1,2-diamino-2-methylpropane, 1,2-diaminocyclohexane, 1,2-diaminopropane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,7-diaminoheptane, 1,8-diaminomenthane, 1,8-diaminooctane, 1,9-diaminononane, 3,3′-diamino-N-methyldipropylamine, diaminomaleonitrile, 1,3-diaminopentane, bis(4-amino-3-methylcyclohexyl)methane, 1,2-bis(2-aminoethoxy)ethane, and 3(4),8(9)-bis(aminomethyl)tricyclo(5.2.1.02,6)decane.
[0110] Among the aliphatic diamine compounds, dimer diamine is preferred from the viewpoints of light transmittance, flexibility, and compatibility between the resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain and solvents and other components. That is, the resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain preferably has an aliphatic group derived from dimer diamine.
[0111] Specific examples of the dimer diamine include dimer diamines capable of forming at least one group selected from the group represented by formula (2-1), the group represented by formula (2-2), the group represented by formula (2-3), and the group represented by formula (2-4).
[0112] Examples of the aromatic diamine compound include 9,10-diaminophenanthrene, 4,4'-diaminooctafluorobiphenyl, 3,7-diamino-2-methoxyfluorene, 4,4'-diaminobenzophenone, 3,4-diaminobenzophenone, 3,4-diaminotoluene, 2,6-diaminoanthraquinone, 2,6-diaminotoluene, 2,3-diaminotoluene, 1,8-diaminonaphthalene, 2,4-diaminotoluene, 2,5-diaminotoluene, 1,4-diaminoanthraquinone, 1,5 -Diaminoanthraquinone, 1,5-diaminonaphthalene, 1,2-diaminoanthraquinone, 2,4-isopropylphenylenediamine, 1,3-bisaminotoluene, 1,3-bisaminomethylcyclohexane, 2-chloro-1,4-diaminobenzene, 1,4-diamino-2,5-dichlorobenzene, 1,4-diamino-2,5-dimethylbenzene, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, bis(amino-3-chlorophenyl)ethane, bis(4-amino-3,5-dimethylphenyl)methane, bis( 4-amino-3,5-diethylphenyl)methane, bis(4-amino-3-ethyldiaminofluorene, 2,3-diaminonaphthalene, 2,3-diaminophenol, -5-methylphenyl)methane, bis(4-amino-3-methylphenyl)methane, bis(4-amino-3-ethylphenyl)methane, 4,4'-diaminophenyl sulfone, 3,3'-diaminophenyl sulfone, 2,2-bis(4, (4-aminophenoxy) phenyl) sulfone, 2,2-bis(4- (3-aminophenoxy) phenyl) sulfone , 4,4'-oxydiphenylamine, 4,4'-diaminodiphenyl sulfide, 3,4'-oxydiphenylamine, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-diamino-3,3'-dihydroxybiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-3,3'-dimethoxybiphenyl, Bisaniline M, Bisaniline P, 9,9-bis(4-aminophenyl)fluorene, o-tolidine sulfone, methylenebis(o-aminobenzoic acid), 1,3-bis(4-aminophenoxy)-2,2-dimethylpropane, 1,3-bis(4-aminophenoxy)propane, 1,4-bis(4-aminophenoxy)butane, 1,5-bis(4-aminophenoxy)butane, 2,3,5,6-tetramethyl-1,4-phenylenediamine, 3,3',5,5'-tetramethylbenzidine, 4,4'-diaminobenzanilide, 2,2-bis(4-aminophenyl)hexafluoropropane, polyoxyalkylene diamines (e.g., Jeffamine D-230, D-400, D-2000 and D-4000 manufactured by Huntsman Co.), 1,3-cyclohexanebis(methylamine), m-xylylenediamine, p-xylylenediamine, and the like.
[0113] Examples of the aromatic acid anhydride include pyromellitic acid, 1,2,5,6-naphthalenetetracarboxylic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 1,2,4,5-naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-biphenyl ethertetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,5,6-pyridinetetracarboxylic acid, Formic acid, 3,4,9,10-perylenetetracarboxylic acid, 4,4'-sulfonyldiphthalic acid, 1-trifluoromethyl-2,3,5,6-benzenetetracarboxylic acid, 2,2',3,3'-biphenyltetracarboxylic acid, 2,2-bis(3,4-dicarboxyphenyl)propane, 2,2-bis(2,3-dicarboxyphenyl)propane, 1,1-bis(2,3-dicarboxyphenyl)ethane, 1,1-bis(3,4- bis(2,3-dicarboxyphenyl)ethane, bis(2,3-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl)sulfone, bis(3,4-dicarboxyphenyl)ether, benzene-1,2,3,4-tetracarboxylic acid, 2,3,2',3'-benzophenonetetracarboxylic acid, 2,3,3',4'-benzophenonetetracarboxylic acid, phenanthrene-1,8,9,10-tetracarboxylic acid, pyrazine- Anhydrides of carboxylic acids such as 2,3,5,6-tetracarboxylic acid, thiophene-2,3,4,5-tetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, 3,4,3',4'-biphenyltetracarboxylic acid, 2,3,2',3'-biphenyltetracarboxylic acid, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide, and 4,4'-(4,4'-isopropylidene diphenoxy)-bis(phthalic acid).
[0114] The above-mentioned resin having an imide skeleton in the repeating unit of the main chain in 100 parts by mass of the above-mentioned resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain is preferably limited to 10 parts by mass, and the preferred upper limit is 90 parts by mass. By making the content of the above-mentioned resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain within the range, the temporary fixing material using the obtained resin composition can be more easily peeled off when peeled off from the adherend. From the viewpoint of further improving the peelability, the above-mentioned resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain is more preferably limited to 20 parts by mass, and the preferred upper limit is 80 parts by mass.
[0115] The resin composition of the present invention may be thermosetting or photocurable, or may be non-curable.
[0116] In the case where the resin composition of the present invention is thermosetting or photocurable, the resin having an imide skeleton in the repeating unit of the main chain preferably includes a resin having a reactive functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain. By including the above-mentioned reactive functional group having a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain, the obtained resin composition is uniformly and rapidly polymerized and cross-linked as a whole by heating or light irradiation, and the elastic modulus rises, thereby greatly reducing the adhesive force. Therefore, it is possible to prevent the temporary fixing material using the obtained resin composition from causing excessive adhesion or residual glue when peeling.
[0117] In the case where the above-mentioned resin having an imide skeleton in the repeating units of the main chain includes the above-mentioned resin having no maleimide group and having an imide skeleton in the repeating units of the main chain, in addition to the above-mentioned resin having no maleimide group and having an imide skeleton in the repeating units of the main chain, it can also include the above-mentioned resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating units of the main chain.
[0118] Examples of the reactive functional group having a carbon-carbon double bond include a maleimide group which may be substituted, a citraconimide group, a vinyl ether group, an allyl group, a (meth)acryloyl group, etc. Among them, a maleimide group which may be substituted is preferred from the viewpoint of obtaining higher heat resistance.
[0119] In addition, in this specification, the said (meth)acryloyl group means an acryloyl group or a methacryloyl group.
[0120] The above-mentioned resin having a reactive functional group with a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain preferably has a functional group equivalent (weight average molecular weight / number of reactive functional groups with a carbon-carbon double bond) of a reactive functional group with a carbon-carbon double bond of 4000 or less. By making the functional group equivalent of the above-mentioned reactive functional group with a carbon-carbon double bond less than 4000, the heat resistance of the obtained resin composition becomes more excellent. It is believed that this is because by having a reactive functional group with a carbon-carbon double bond at a density above a certain level in the molecule of the resin, the distance between crosslinks becomes shorter, thereby further suppressing hyperadhesion. The functional group equivalent of the above-mentioned reactive functional group with a carbon-carbon double bond is more preferably less than 3000, and more preferably less than 2000.
[0121] In addition, the preferred lower limit of the functional group equivalent of the reactive functional group having a carbon-carbon double bond is not particularly limited, but the substantial lower limit is about 600.
[0122] The weight average molecular weight of the resin having a reactive functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain is preferably 1000 or more and 100,000 or less. By making the weight average molecular weight of the resin having a reactive functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain more than 1000, the film formation of the obtained resin composition becomes easy, and the temporary fixing material using the obtained resin composition exerts a certain degree of softness, so that it can exert high followability to the adherend with unevenness, and can be more easily peeled off when peeling. By making the weight average molecular weight of the resin having a reactive functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain less than 100,000, the solubility of the resin having a reactive functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain in the solvent can be prevented from becoming too low. The weight average molecular weight of the resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in a repeating unit of the main chain is more preferably 1,500 to 50,000, and further preferably 2,000 to less than 20,000.
[0123] In the above-mentioned resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, the reactive functional group having a carbon-carbon double bond can be located at any position in the side chain or the terminal, preferably at both terminals, and more preferably at the side chain in addition to both terminals.
[0124] The reactive functional groups having carbon-carbon double bonds at both ends of the resin having an imide skeleton in the repeating unit of the main chain are highly reactive, and the resin composition can be cured more fully by irradiation with light, etc. As a result, it is possible to further prevent excessive adhesion or residual adhesive from being generated during peeling.
[0125] In addition, by having reactive functional groups with carbon-carbon double bonds in the side chain of the resin with imide skeleton in the repeating unit of the main chain, the heat resistance of the obtained resin combination becomes more excellent. It is believed that this is because, by shortening the distance between crosslinks, it is possible to further suppress hyperadhesion. In addition, by having reactive functional groups with carbon-carbon double bonds in the side chain of the resin with imide skeleton in the repeating unit of the main chain, it is possible to easily make the above-mentioned weight-average molecular weight more than 1000, and the above-mentioned functional group equivalent is adjusted to less than 4000. Thus, the obtained resin combination has sufficient initial adhesion, and it is possible to further prevent hyperadhesion or produce residual glue when peeling.
[0126] As described above, in the above-mentioned resin having a reactive functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain, the reactive functional group with a carbon-carbon double bond can be located at any position in the side chain or the terminal. In the case where any of the side chain or the terminal is a functional group other than a reactive functional group with a carbon-carbon double bond (a functional group without a carbon-carbon double bond), as the functional group without a carbon-carbon double bond, for example, an aliphatic group, an alicyclic group, an aromatic group, an acid anhydride group, an amino group, etc. can be cited. Specifically, it can be cited: an acid anhydride that becomes the raw material of the above-mentioned resin having a reactive functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain, an unreacted single-terminal constituent group of a diamine compound, etc. When the resin having the reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain has two or more functional groups not having a carbon-carbon double bond in the side chain or at the terminal, the functional groups not having a carbon-carbon double bond may be the same or different.
[0127] Specific examples of the resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in a repeating unit of the main chain include a resin having a structural unit represented by the above formula (1) and having a reactive functional group having a carbon-carbon double bond at at least one position of a terminal and a side chain.
[0128] The resin having the structural unit represented by the above formula (1) and having a reactive functional group having a carbon-carbon double bond at at least one position of the terminal and the side chain may have at least one structural unit selected from the structural unit represented by the following formula (4-1) and the structural unit represented by the following formula (4-2).
[0129] [Chemical formula 4]
[0130]
[0131] In formula (4-1), P 3 represents an aromatic group, Q 3 represents a substituted or unsubstituted group having an aromatic structure, in formula (4-2), P 4 represents an aromatic group, R represents a substituted or unsubstituted branched aliphatic group or aromatic group, and X represents a reactive functional group having a carbon-carbon double bond.
[0132] In the above formula (4-1), P 3 and P in the above formula (4-2) 4 It is preferably an aromatic group having 5 to 50 carbon atoms. 3 and P 4The aromatic group has 5 to 50 carbon atoms, so that the heat resistance of the obtained resin composition becomes better. That is, the temporary fixing material using the obtained resin composition can further suppress the generation of gaps and floating between the support body during the heating treatment at high temperature, and can further prevent the adhesion to the adherend from being excessive or the generation of residual adhesive when peeling from the adherend.
[0133] In the above formula (4-1), Q 3 It is preferably a substituted or unsubstituted group having 5 to 50 carbon atoms and having an aromatic structure. 3 The present invention is a substituted or unsubstituted group having an aromatic structure and having 5 to 50 carbon atoms, so that the heat resistance of the obtained resin composition is further improved. That is, the temporary fixing material using the obtained resin composition can further suppress the generation of gaps and floating between the support body during the heating treatment at high temperature, and can further prevent the adhesion to the adherend from being excessive or the generation of residual adhesive when peeling from the adherend.
[0134] In the above formula (4-2), R is preferably a substituted or unsubstituted branched aliphatic group or aromatic group having 2 to 100 carbon atoms. By making the above R a substituted or unsubstituted branched aliphatic group or aromatic group having 2 to 100 carbon atoms, the obtained resin composition has better flexibility, and the temporary fixing material using the resin composition can exhibit high followability to the adherend having unevenness and can be more easily peeled off when peeling.
[0135] In the above formula (4-2), R is an aromatic group having an aromatic ester group or an aromatic ether group, and the aromatic ester group or the aromatic ether group in R is preferably bonded to X.
[0136] Here, "aromatic ester group" refers to a group with an ester group directly bonded to an aromatic ring, and "aromatic ether group" refers to a group with an ether group directly bonded to an aromatic ring. By making the part bonded to the ester group and the ether group an aromatic group in this way, the heat resistance of the obtained resin composition becomes more excellent. That is, the temporary fixing material using the obtained resin composition can further suppress the generation of voids and floating during the heating treatment at high temperature, and can further prevent the adhesion to the adherend from being caused by hyperadhesion or residual glue when peeling from the adherend. On the other hand, by bonding X to R via an aromatic ester group or an aromatic ether group, the carbon-carbon double bond in X will not be conjugated with R, and therefore will not hinder the polymerization crosslinking during heating or irradiation with light.
[0137] The content ratio of the structural unit represented by the above formula (1) in the resin having the structural unit represented by the above formula (1) and having a reactive functional group having a carbon-carbon double bond at at least any position of the terminal and the side chain is preferably 30 mol% or more, more preferably 50 mol% or more, and preferably 90 mol% or less, more preferably 80 mol% or less.
[0138] When the resin having the structural unit represented by the above formula (1) and having a reactive functional group having a carbon-carbon double bond at at least any position of the terminal and the side chain has the structural unit represented by the above formula (4-1), the content ratio of the structural unit represented by the above formula (4-1) is preferably 5 mol% or more, more preferably 10 mol% or more, further preferably 20 mol% or more, preferably 50 mol% or less, more preferably 30 mol% or less.
[0139] When the resin having the structural unit represented by the above formula (1) and having a reactive functional group having a carbon-carbon double bond at at least any position of the terminal and the side chain has the structural unit represented by the above formula (4-2), the content ratio of the structural unit represented by the above formula (4-2) is preferably 10 mol% or more, more preferably 20 mol% or more, preferably 50 mol% or less, more preferably 30 mol% or less.
[0140] By setting the content of each structural unit in the structural unit represented by the above formula (1), the structural unit represented by the above formula (4-1) and the structural unit represented by the above formula (4-2) to be within the above range, the temporary fixing material using the obtained resin composition can further suppress the generation of voids and floating between the support and the adhesive during heat treatment at high temperature, and can be more easily peeled off from the adherend.
[0141] It should be noted that the structural unit represented by the above formula (1), the structural unit represented by the above formula (4-1), and the structural unit represented by the above formula (4-2) may have a block structure including block components in which the structural units are continuously arranged, or may have a random structure in which the structural units are randomly arranged.
[0142] Examples of a method for producing the resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in a repeating unit of the main chain include the following method.
[0143] That is, first, a diamine compound is reacted with an aromatic acid anhydride to prepare an imide compound. Next, a functional group of the imide compound is reacted with a compound having a functional group reactive with the functional group and a reactive functional group having a carbon-carbon double bond (hereinafter also referred to as a "functional group-containing unsaturated compound"), thereby obtaining the resin having the reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain.
[0144] Alternatively, a resin having a reactive functional group having a carbon-carbon double bond and an imide skeleton in a repeating unit of the main chain can be obtained by reacting a diamine compound with an aromatic anhydride to prepare an imide compound and reacting the terminal of the imide compound with, for example, maleic anhydride.
[0145] As the diamine compound and aromatic anhydride used in the method for producing the above-mentioned resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, the same diamine compound and aromatic anhydride as those used in the method for producing the above-mentioned resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain can be used.
[0146] The functional group-containing unsaturated compound is selected and used according to the functional group at the terminal or side chain of the imide compound.
[0147] For example, when the functional group of the terminal or side chain of the above-mentioned imide compound is a hydroxyl group, examples of the above-mentioned functional group-containing unsaturated compound include: a maleimide compound having a carboxyl group, a vinyl compound having an ether group, an allyl compound having a glycidyl group, an allyl ether compound having a glycidyl group, a vinyl ether compound having a glycidyl group, an allyl compound having an isocyanate group, and a (meth)acryloyl compound having an isocyanate group.
[0148] In addition, for example, when the functional group of the terminal or side chain of the above-mentioned imide compound is a carboxyl group, examples of the above-mentioned functional group-containing unsaturated compound include: allyl compounds having a hydroxyl group, allyl compounds having a glycidyl group, allyl ether compounds having a glycidyl group, vinyl ether compounds having a glycidyl group, etc.
[0149] Examples of the maleimide compound having a carboxyl group include acetic maleimide, maleimidopropionic acid, maleimidobutyric acid, maleimidohexanoic acid, trans-4-(N-maleimidomethyl)cyclohexane-1-carboxylic acid, and 19-maleimido-17-oxo-4,7,10,13-tetraoxa-16-azanonadecanoic acid.
[0150] Examples of the vinyl compound having an ether group include butyl vinyl ether and the like.
[0151] Examples of the allyl compound having a glycidyl group include diallyl monoglycidyl isocyanurate and the like.
[0152] Examples of the allyl ether compound having a glycidyl group include allyl glycidyl ether and glycerol diallyl monoglycidyl ether.
[0153] Examples of the vinyl ether compound having a glycidyl group include glycidyloxyethyl vinyl ether, glycidyloxybutyl vinyl ether, glycidyloxyhexyl vinyl ether, glycidyl diethylene glycol vinyl ether, and glycidyl cyclohexanedimethanol monovinyl ether.
[0154] As the allyl compound having an isocyanate group, for example, allyl isocyanate etc. can be mentioned.
[0155] As a (meth)acryloyl compound which has the said isocyanate group, 2-(meth)acryloyloxyethyl isocyanate etc. are mentioned, for example.
[0156] Examples of the allyl compound having a hydroxyl group include trimethylolpropane diallyl ether and pentaerythritol triallyl ether.
[0157] In 100 parts by mass of the resin having an imide skeleton in the repeating unit of the main chain, the preferred lower limit of the content of the resin having a reactive functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain is 10 parts by mass, and the preferred upper limit is 100 parts by mass. By making the content of the resin having a reactive functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain within the range, the temporary fixing material using the obtained resin composition can be more easily peeled off when peeling off. From the viewpoint of further improving the peelability, the more preferred lower limit of the content of the resin having a reactive functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain is 20 parts by mass, and the further preferred lower limit is 30 parts by mass, and the more preferred upper limit is 90 parts by mass, and the further preferred upper limit is 80 parts by mass, and the further preferred upper limit is 70 parts by mass.
[0158] In the case where the above-mentioned resin having an imide skeleton in the repeating units of the main chain includes the above-mentioned resin having no maleimide group and having an imide skeleton in the repeating units of the main chain, the resin composition of the present invention preferably further comprises: a polyfunctional monomer or polyfunctional oligomer having two or more reactive functional groups having carbon-carbon double bonds in the molecule and a molecular weight of 5000 or less (hereinafter also referred to as "polyfunctional monomer or polyfunctional oligomer").
[0159] In addition, when the resin having an imide skeleton in the repeating unit of the main chain includes the resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, the resin composition of the present invention may further include the polyfunctional monomer or polyfunctional oligomer.
[0160] By including the above-mentioned multifunctional monomer or multifunctional oligomer, the obtained resin composition can be more efficiently three-dimensionally networked by light irradiation or the like, and can further prevent excessive adhesion and residual adhesive from being generated during peeling.
[0161] The molecular weight of the polyfunctional monomer or polyfunctional oligomer is more preferably less than 5,000.
[0162] It should be noted that, in the case where the resin having an imide skeleton in the repeating unit of the main chain itself is not reactive, the resin composition of the present invention further contains other components with reactive functional groups, thereby enabling the above-mentioned resin composition as a whole to be reactive. As such other components with reactive functional groups, it is preferred to use the above-mentioned multifunctional monomers or multifunctional oligomers. As the case where the resin having an imide skeleton in the repeating unit of the main chain itself is not reactive, for example, the resin having an imide skeleton in the repeating unit of the main chain only includes the above-mentioned resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain.
[0163] As the reactive functional group having a carbon-carbon double bond in the above-mentioned multifunctional monomer or multifunctional oligomer, for example, there can be mentioned: a maleimide group, a citraconimide group, a vinyl ether group, an allyl group, a (meth)acryloyl group, etc. which may be substituted. Among them, a maleimide group which may be substituted is suitable from the aspect of being able to obtain higher heat resistance. In particular, the above-mentioned multifunctional monomer or multifunctional oligomer is preferably a bismaleimide compound.
[0164] The above-mentioned multifunctional monomer or multifunctional oligomer preferably has a group from a diamine compound. As the above-mentioned diamine compound, any of an aliphatic diamine compound or an aromatic diamine compound can be used, preferably an aliphatic diamine compound. That is, the above-mentioned multifunctional monomer or multifunctional oligomer more preferably has an aliphatic group from a diamine compound. By using an aliphatic diamine compound as the above-mentioned diamine compound, the light transmittance of the obtained resin composition becomes more excellent. In addition, the softness of the obtained resin composition becomes more excellent, and the temporary fixing material using the obtained resin composition can exert high tracking properties on an adherend with unevenness, and can be more easily peeled off when peeling off.
[0165] Among the aliphatic diamine compounds, the dimer diamines described above are preferred from the viewpoints of light transmittance, flexibility, and compatibility of the polyfunctional monomer or polyfunctional oligomer with a solvent and other components.
[0166] In the total of 100 parts by mass of the resin having an imide skeleton in the repeating unit of the main chain and the polyfunctional monomer or polyfunctional oligomer, the preferred lower limit of the content of the polyfunctional monomer or polyfunctional oligomer is 5 parts by mass, and the preferred upper limit is 90 parts by mass. By making the content of the polyfunctional monomer or polyfunctional oligomer within the range, the resulting resin composition can be more easily peeled off when peeling off. From the viewpoint of further improving peelability, the more preferred lower limit of the content of the polyfunctional monomer or polyfunctional oligomer is 10 parts by mass, and the more preferred upper limit is 50 parts by mass.
[0167] As the resin having an imide skeleton in the repeating unit of the main chain, in the case of containing the resin having no reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, and the resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, and including the polyfunctional monomer or polyfunctional oligomer, the preferred lower limit of the total content of the resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain and the polyfunctional monomer or polyfunctional oligomer is 20 parts by mass, and the preferred upper limit is 80 parts by mass. By making the total content of the resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain and the polyfunctional monomer or polyfunctional oligomer within this range, the obtained resin composition can be more easily peeled off when peeling off. From the viewpoint of further improving the peelability, the more preferred lower limit of the total content of the resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain and the above-mentioned polyfunctional monomer or polyfunctional oligomer is 30 parts by mass, a further preferred lower limit is 40 parts by mass, a further preferred lower limit is 50 parts by mass, and a more preferred upper limit is 70 parts by mass.
[0168] The resin composition of the present invention preferably contains a compound having a maleimide group. By containing the compound having a maleimide group, the heat resistance of the obtained resin composition becomes more excellent.
[0169] The compound having a maleimide group is preferably the polyfunctional monomer or polyfunctional oligomer having a maleimide group, or a resin having a maleimide group and having an imide skeleton in the repeating unit of the main chain. That is, preferably, the resin composition of the present invention comprises a compound having a maleimide group as the polyfunctional monomer or polyfunctional oligomer, or the resin composition of the present invention comprises a resin having a maleimide group as the reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain.
[0170] Among them, in the resin composition of the present invention, as the resin having a maleimide group and having an imide skeleton in the repeating unit of the main chain, it is preferred to contain: a resin having a structural unit represented by the above formula (1) and having a functional group having a maleimide group at at least one position of the terminal and the side chain. In addition, the above multifunctional monomer or multifunctional oligomer having a maleimide group is preferably a bismaleimide compound.
[0171] The resin composition of the present invention preferably further comprises a polymerization initiator. The polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator, and is preferably a photopolymerization initiator.
[0172] As the above-mentioned photopolymerization initiator, for example, a photopolymerization initiator activated by irradiation with light of a wavelength of 250 to 800 nm can be cited. Among them, from the perspective of not easily overlapping with the absorption wavelength of the above-mentioned resin having a reactive functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, the above-mentioned multifunctional monomer or multifunctional oligomer, and being fully activated when the resin composition is irradiated with light, the above-mentioned photopolymerization initiator preferably contains a compound having a molar absorption coefficient of 1 or more at 365 nm. The above-mentioned photopolymerization initiator more preferably contains a compound having a molar absorption coefficient of 200 or more at 365 nm, and further preferably contains a compound having a molar absorption coefficient of 350 or more at 365 nm. The preferred upper limit of the molar absorption coefficient at 365 nm of the compound having a molar absorption coefficient of 1 or more at 365 nm is not particularly limited, and the actual upper limit is 2000.
[0173] Examples of the photopolymerization initiator include acetophenone derivatives, benzoin ether compounds, ketal derivatives, and phosphine oxide derivatives.
[0174] Examples of the acetophenone derivative include methoxyacetophenone and the like.
[0175] Examples of the benzoin ether compound include benzoin propyl ether and benzoin isobutyl ether.
[0176] Examples of the ketal derivative include benzyl dimethyl ketal and acetophenone diethyl ketal.
[0177] Examples of the phosphine oxide derivative include diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide and the like.
[0178] In addition, examples of the photopolymerization initiator include bis(η5-cyclopentadienyl)titanocene derivative compounds, benzophenone, Michler's ketone, chlorothioxanthone, dodecylthioxanthone, dimethylthioxanthone, diethylthioxanthone, α-hydroxycyclohexyl phenyl ketone, and 2-hydroxymethylphenylpropane.
[0179] These photopolymerization initiators may be used alone or in combination of two or more.
[0180] Relative to the total 100 mass parts of the resin having an imide skeleton in the repeating unit of the main chain and the above-mentioned multifunctional monomer or multifunctional oligomer, the preferred lower limit of the content of the above-mentioned polymerization initiator is 0.1 mass parts, and the preferred upper limit is 10 mass parts. By making the content of the above-mentioned polymerization initiator within the range, the overall structure of the above-mentioned resin composition is uniformly and rapidly polymerized and cross-linked due to the irradiation of light, etc., and the adhesive force is greatly reduced due to the rise in elastic modulus, which can prevent the occurrence of hyperadhesion or residual glue when peeling. The more preferred lower limit of the content of the above-mentioned polymerization initiator is 0.3 mass parts, and the more preferred upper limit is 3 mass parts.
[0181] The resin composition of the present invention may further contain a gas generator. By containing the gas generator, even after heat treatment at a high temperature of 300°C or more, the gas generated by irradiation with light is released to the interface with the adherend, so that the adherend can be peeled off more easily without residual adhesive. In addition, even in the case of peeling a thin adherend after heat treatment at a high temperature of 300°C or more, damage to the adherend can be prevented.
[0182] The gas generating agent preferably has a weight reduction rate of 5% or less at 300°C when heated from 30°C to 300°C at a heating rate of 10°C / min in a nitrogen atmosphere in a TG-DTA (thermogravimetric-differential thermal analysis) measurement. If the weight reduction rate is 5% or less, the gas generating agent is less likely to decompose even when subjected to a high temperature heating treatment of 300°C or higher, and the heat resistance of the obtained resin composition becomes more excellent. That is, the temporary fixing material using the obtained resin composition can further suppress peeling during the high temperature heating treatment, and can further prevent the occurrence of excessive adhesion or the generation of residual adhesive during peeling.
[0183] The TG-DTA (thermogravimetric-differential thermal analysis) measurement can be performed using, for example, a TG-DTA apparatus (“STA7200RV” manufactured by Hitachi High-Tech Science Co., Ltd.).
[0184] Examples of the gas generating agent include a gas generating agent that generates gas by heating, a gas generating agent that generates gas by irradiating light, etc. Among them, a gas generating agent that generates gas by irradiating light is preferred, and a gas generating agent that generates gas by irradiating ultraviolet rays is more preferred.
[0185] Examples of the gas generating agent include tetrazole compounds or salts thereof, triazole compounds or salts thereof, azo compounds, azide compounds, xanthone acetic acid, carbonates, etc. These gas generating agents may be used alone or in combination of two or more. Among them, tetrazole compounds or salts thereof are preferred from the perspective of excellent heat resistance.
[0186] The preferred lower limit of the content of the gas generator is 5 parts by mass and the preferred upper limit is 50 parts by mass relative to 100 parts by mass of the total of the resin having an imide skeleton in the repeating unit of the main chain and the multifunctional monomer or multifunctional oligomer. By making the content of the gas generator within this range, the removability of the temporary fixing material using the obtained resin composition becomes particularly excellent. The more preferred lower limit of the content of the gas generator is 8 parts by mass, and the more preferred upper limit is 30 parts by mass.
[0187] The resin composition of the present invention may further contain an inorganic filler.
[0188] By containing the inorganic filler, the elastic modulus of the obtained resin composition at high temperature can be suppressed from decreasing, and even when the temporary fixing material using the obtained resin composition is subjected to heat treatment at high temperature, peeling during heat treatment at high temperature can be further suppressed.
[0189] Examples of the inorganic filler include an inorganic filler containing at least one selected from oxides of silicon, titanium, aluminum, calcium, boron, magnesium and zirconium oxide, and composites thereof. Among them, silicon dioxide and talc are preferred because they are commercially available at low cost and are easily available.
[0190] The inorganic filler may be surface-modified. Examples of the modified functional group for surface-modifying the inorganic filler include alkylsilyl, methacryloyl, and dimethylsiloxane. Among them, dimethylsiloxane is preferred because of its moderate hydrophobicity.
[0191] The preferred lower limit of the average particle size of the inorganic filler is 5 nm, and the preferred upper limit is 30 μm. By making the average particle size of the inorganic filler within this range, the temporary fixing material using the obtained resin composition can further suppress peeling during the heating treatment at high temperature, and can be peeled by peeling treatment during peeling. The more preferred lower limit of the average particle size of the inorganic filler is 10 nm, the more preferred upper limit is 20 μm, the further preferred lower limit is 15 nm, and the further preferred upper limit is 15 μm.
[0192] It should be noted that the average particle size is preferably a number average particle size. The average particle size can be obtained, for example, by observing 50 random inorganic fillers using an electron microscope or an optical microscope and calculating the average particle size of each inorganic filler, or by performing laser diffraction particle size distribution measurement.
[0193] Relative to the total of 100 parts by mass of the resin having an imide skeleton in the repeating unit of the main chain and the multifunctional monomer or multifunctional oligomer, the preferred lower limit of the content of the inorganic filler is 1 part by mass, and the preferred upper limit is 20 parts by mass. By making the content of the inorganic filler within the range, the temporary fixing material using the obtained resin composition can further suppress peeling during the heat treatment at high temperature, and can be peeled off by a peeling treatment when peeling off. The more preferred lower limit of the content of the inorganic filler is 3 parts by mass, the more preferred upper limit is 15 parts by mass, the further preferred lower limit is 5 parts by mass, and the further preferred upper limit is 10 parts by mass.
[0194] The resin composition of the present invention may contain known additives such as a photosensitizer, a heat stabilizer, an antioxidant, an antistatic agent, a plasticizer, a resin, a surfactant, and a wax.
[0195] Examples of a method for producing the resin composition of the present invention include a method of mixing the resin having an imide skeleton in a repeating unit of the main chain, the (meth)acrylic copolymer, and additives blended as required, using a bead mill, ultrasonic dispersion, homogenizer, high-power disperser, roll mill, or the like.
[0196] The preferred lower limit of the 10% weight loss temperature of the resin composition of the present invention is 200° C. By setting the 10% weight loss temperature to 200° C. or higher, the heat resistance of the temporary fixing material using the obtained resin composition becomes more excellent. The more preferred lower limit of the 10% weight loss temperature is 220° C., and the further preferred lower limit is 250° C.
[0197] The upper limit of the 10% weight loss temperature is not particularly limited, but is substantially 600° C. When the temporary fixing material has curability as described below, the 5% weight loss temperature of the cured product of the temporary fixing material is preferably within the above range.
[0198] It should be noted that the 10% weight loss temperature can be measured using a differential thermal thermogravimetric simultaneous measurement device. Specifically, it can be measured by the following method.
[0199] That is, first, the resin composition is weighed into an aluminum pan. If the resin composition is thermosetting or photocurable, the resin composition is heated in an oven at 150°C for 10 minutes or irradiated for 300 seconds at a wavelength of 365 nm and an irradiation intensity of 70 mW / cm 2 The resin composition is cured by ultraviolet rays, and the obtained cured product is weighed into an aluminum pan. Next, the aluminum pan is placed in a differential thermal and thermogravimetric simultaneous measuring device, and when the temperature is increased from 30°C to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, the temperature at which the weight of the cured product is reduced by 10% compared to before the temperature increase is obtained as the 10% weight reduction temperature. As the differential thermal and thermogravimetric simultaneous measuring device, STA7200RV (manufactured by Hitachi High-Tech Science Co., Ltd.) can be used.
[0200] In the case where the resin composition of the present invention is thermosetting or photocurable, the preferred lower limit of the gel fraction after curing of the resin composition of the present invention is 70% by mass, and the preferred upper limit is 95% by mass. By making the gel fraction after the above-mentioned curing within the above-mentioned range, the temporary fixing material using the obtained resin composition can be more easily peeled off when peeling off from the adherend. The more preferred lower limit of the gel fraction after the above-mentioned curing is 75% by mass, and the more preferred upper limit is 90% by mass.
[0201] It should be noted that the gel fraction after curing is determined by irradiating the resin composition with light at a wavelength of 365 nm and an irradiation intensity of 70 mW / cm for 300 seconds when the resin composition is photocurable. 2 The resin composition was cured by ultraviolet rays. If the resin composition was thermosetting, it was cured by heating at 150° C. for 10 minutes and then measured by the following method.
[0202] That is, first, the cured resin composition is cut into a plane rectangle of 50 mm × 100 mm to make a test piece. After the obtained test piece is immersed in toluene at 23 ° C for 24 hours, it is taken out from toluene and dried at 110 ° C for 1 hour. The mass of the dried test piece is measured, and the gel fraction is calculated using the following formula. It should be noted that the spacer for protecting the temporary fixing material is not stacked on the test piece. In addition, when the temporary fixing material does not have a substrate, it is set to W0 = 0.
[0203] Gel fraction (mass %) = 100 × (W2-W0) / (W1-W0)
[0204] (W0: mass of substrate, W1: mass of test piece before immersion, W2: mass of test piece after immersion and drying)
[0205] The resin composition of the present invention is suitable for temporary fixing of electronic components. A temporary fixing material containing the resin composition of the present invention is also one of the present invention.
[0206] The form of the temporary fixing material of the present invention is not particularly limited, and may be in a liquid, paste, or other form, or may be in a form having an adhesive layer comprising the resin composition of the present invention, wherein preferably, the temporary fixing material has an adhesive layer comprising the resin composition of the present invention. In addition, in the case of the temporary fixing material having the above-mentioned adhesive layer, it is preferably in a tape shape.
[0207] In the case of the temporary fixing material having the above-mentioned adhesive layer, the above-mentioned adhesive layer may be provided on one or both sides of the base material, or the base material may not be provided. In the case of not having the above-mentioned base material, there is no need to select a base material having both light transmittance and heat resistance, and the above-mentioned temporary fixing material can be set to a cheaper and simpler structure. In the case of having the above-mentioned base material, the handling property of the temporary fixing material of the present invention is further improved.
[0208] In the case of the substrate, for example, the substrate includes resin sheets such as acrylic resin (Japanese: アクリル), olefin, polycarbonate, vinyl chloride, ABS, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), nylon, urethane, polyimide, polyetheretherketone (PEEK), polyamide (PA), etc., and a resin sheet with high light transmittance can be preferably used. In addition, a sheet having a mesh structure, a sheet with holes, glass, etc. can also be used.
[0209] From the viewpoint of improving light transmittance and flexibility, the thickness of the substrate has a preferred lower limit of 5 μm, more preferably 10 μm, and a preferred upper limit of 150 μm, more preferably 100 μm.
[0210] The method for manufacturing the temporary fixing material of the present invention is not particularly limited. For example, the resin composition obtained by the above method is applied to the release-treated surface of a PET film subjected to single-sided release treatment using an applicator or the like and dried to form an adhesive layer containing the resin composition. Then, another PET film subjected to single-sided release treatment is overlapped in a manner such that the release-treated surface and the adhesive layer are opposite to each other, thereby obtaining a temporary fixing material with a release PET film without a substrate as a temporary fixing material in the form of an adhesive layer.
[0211] Furthermore, after forming the adhesive layer by the above method, by overlaying the substrate and the adhesive layer so as to face each other, a temporary fixing material with a release PET film having a substrate can be obtained.
[0212] In the case where the temporary fixing material of the present invention is a temporary fixing material having the above-mentioned adhesive layer, the preferred lower limit of the thickness of the temporary fixing material as a whole of the present invention is 5μm, and the preferred upper limit is 550μm. By making the thickness of the above-mentioned temporary fixing material above 5μm or more, the above-mentioned temporary fixing material as a whole can have sufficient pressure-sensitive or heat-sensitive adhesive force in the initial stage. By making the thickness of the above-mentioned temporary fixing material as a whole below 550μm, the above-mentioned temporary fixing material as a whole can exhibit high flexibility, can exhibit high followability to the adherend with unevenness, and can be peeled off more easily when peeling. The more preferred lower limit of the thickness of the above-mentioned temporary fixing material as a whole is 10μm, the further preferred lower limit is 20μm, and the further preferred lower limit is 30μm. The more preferred upper limit of the thickness of the above-mentioned temporary fixing material as a whole is 400μm, the further preferred upper limit is 300μm, the further preferred upper limit is 200μm, and the particularly preferred upper limit is 150μm.
[0213] The preferred lower limit of the initial adhesive force of the temporary fixing material of the present invention to polyimide at 25°C is 0.1N / inch, and the preferred upper limit is 1.5N / inch. By setting the initial adhesive force to polyimide at 25°C to this range, the temporary fixing material of the present invention can further prevent excessive adhesion to the adherend having polyimide on the surface after heat treatment at high temperature, or prevent residual adhesive from being generated during peeling, and can be peeled off more easily during peeling off the adherend having polyimide on the surface. The more preferred lower limit of the initial adhesive force to polyimide at 25°C is 0.2N / inch, and the more preferred upper limit is 1.2N / inch.
[0214] In addition, the preferred lower limit of the adhesive force of the temporary fixing material of the present invention to polyimide at 25°C after heating at 250°C for 2 hours is 0.01N / inch, and the preferred upper limit is 1.5N / inch. By making the above-mentioned adhesive force to polyimide at 25°C after heating at 250°C for 2 hours within this range, the temporary fixing material of the present invention can further prevent the adhesion to the adherend having polyimide on the surface after the heat treatment at high temperature, or the generation of residual adhesive during peeling, and can be more easily peeled off when peeling off the adherend having polyimide on the surface. The more preferred lower limit of the adhesive force to polyimide at 25°C after heating at 250°C for 2 hours is 0.1N / inch, and the more preferred upper limit is 1N / inch.
[0215] The adhesive force to polyimide is measured by the following method.
[0216] That is, first, the temporary fixing material is laminated on the polyimide by a laminator to obtain a laminate. As the polyimide, for example, Upilex (manufactured by UBE) or Kapton (manufactured by TORAY DUPONT) can be used, and as the laminator, Leon13DX (manufactured by LAMI Corporation, speed grade (Japanese: Speed メモリ) 5) can be used. In the case where a thermosetting or photocurable resin composition is used as the temporary fixing material, after lamination, it is heated in an oven at 150°C for 10 minutes, or irradiated for 300 seconds at a wavelength of 365nm and an irradiation intensity of 70mW / cm 2 The temporary fixing material is cured by ultraviolet rays to obtain a laminate. The obtained laminate is subjected to a peel test using a tensile testing machine at 25°C, a tensile angle of 30°, and a tensile speed of 300 mm / min, thereby measuring the initial adhesion to polyimide at 25°C. As the above-mentioned tensile testing machine, an angle-free adhesion-film peeling analysis device VPA-2S (manufactured by Kyowa Interface Science Co., Ltd.) can be used. Regarding the adhesion to polyimide at 25°C after heating at 250°C for 2 hours, the adhesion of the temporary fixing material to polyimide is similarly measured after the obtained laminate is heated at 250°C for 2 hours.
[0217] The temporary fixing material of the present invention can prevent the adherend from being excessively adhered after being heated at high temperature, or from producing residual adhesive when being peeled off, and can be easily peeled off when being peeled off from the adherend. Therefore, the temporary fixing material of the present invention can be suitable for protecting and temporarily fixing adherends to be heated at high temperature, especially adherends having polyimide on the surface. Especially when processing electronic components such as semiconductors, in order to make the processing of electronic components easy and not damaged, it can be suitable for fixing the electronic components to a support plate with the help of the above-mentioned temporary fixing material, or attaching the above-mentioned temporary fixing material to the electronic components for protection.
[0218] A method for manufacturing an electronic component including a temporary fixing step of temporarily fixing an electronic component to a temporary fixing material of the present invention, a heat treatment step of heat-treating the electronic component, and a stripping step of stripping the electronic component from the temporary fixing material of the present invention is also one of the present invention. In the case where a thermosetting or photocurable resin composition is used as the temporary fixing material of the present invention, it is preferred that a curing step of curing the temporary fixing material is included between the temporary fixing step and the heat treatment step. By performing the curing step between the temporary fixing step and the heat treatment step, the temporary fixing material can exhibit better heat resistance.
[0219] Effects of the Invention
[0220] According to the present invention, a resin composition that can suppress the generation of voids and floating during heat treatment and can be easily peeled off after heat treatment can be provided. In addition, according to the present invention, a temporary fixing material comprising the resin composition and a method for manufacturing an electronic component using the temporary fixing material can be provided. DETAILED DESCRIPTION
[0221] Hereinafter, the embodiment of the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0222] (Synthesis example 1)
[0223] 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 31.9 g (0.06 mol) of dimer diamine (manufactured by Croda, "Priamine 1075"), 5.5 g (0.015 mol) of 2,2-bis(3-amino-4-hydroxyphenyl)-hexafluoropropane, and 39 g (0.0765 mol) of 4,4'-(4,4'-isopropyldiphenoxy)diphthalic anhydride were added in sequence. A Dean-Stark tube and a condenser were installed in the flask, and the obtained mixture was refluxed for 6 hours and cooled to room temperature. A brown resin having a structural unit represented by the following formula (5-1) and a structural unit represented by the following formula (5-2), having no maleimide group and having an imide skeleton in the repeating unit of the main chain (PI (A) without maleimide group) was obtained.
[0224] The obtained PI (A) not containing a maleimide group was measured by gel permeation chromatography (GPC, apparatus name: Acquity APC system (manufactured by Waters)) using THF as an eluent and HR-MB-M 6.0×150 mm (manufactured by Waters) as a column. As a result, the weight average molecular weight was 78,000.
[0225] [Chemical formula 5]
[0226]
[0227] (Synthesis example 2)
[0228] 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. Next, 35 g (0.35 mol) of triethylamine and 35 g (0.36 mol) of methanesulfonic anhydride were added and stirred to form a salt. After stirring for 10 minutes, 56 g (0.1 mol) of dimer diamine (Croda, Priamine 1075) and 19.1 g (0.09 mol) of pyromellitic anhydride were added in sequence. The Dean-Stark water separator and condenser were installed in the flask, and the mixture was refluxed for 2 hours to form an amine-terminated diimide. After the reactant was cooled to below room temperature, 12.8 g (0.13 mol) of maleic anhydride was added, and then 5 g (0.05 mol) of methanesulfonic anhydride was added. After the obtained mixture was further refluxed for 12 hours, it was cooled to room temperature, 300 mL of toluene was added to the flask, and the layers were separated by standing to remove the lower layer as an impurity. The obtained solution was filtered through a glass frit funnel filled with silica gel, and the solvent was removed in vacuo to obtain an amber waxy resin having maleimide groups at both ends and an imide skeleton in the repeating unit of the main chain (maleimide-containing PI) represented by the following formula (6).
[0229] The obtained maleimide group-containing PI was measured by gel permeation chromatography (GPC, apparatus name: Acquity APC system (manufactured by Waters)) using THF as an eluent and HR-MB-M 6.0×150 mm (manufactured by Waters) as a column. As a result, the weight average molecular weight was 5,000.
[0230] [Chemical formula 6]
[0231]
[0232] In formula (6), n is the number of repetitions.
[0233] (Synthesis example 3)
[0234] 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 56 g (0.1 mol) of dimer diamine (Priamine 1075 manufactured by Croda) and 19.6 g (0.2 mol) of maleic anhydride were added, followed by 5 g of methanesulfonic anhydride. The resulting solution was refluxed for 12 hours, cooled to room temperature, and 300 mL of toluene was added to the flask. The layers were separated by standing to remove the lower layer as impurities. The resulting solution was filtered through a glass funnel filled with silica gel, and the solvent was removed in vacuo to obtain a brown liquid bismaleimide monomer (multifunctional monomer) represented by the following formula (7).
[0235] [Chemical formula 7]
[0236]
[0237] (Synthesis example 4)
[0238] Ethyl acetate was added as a polymerization solvent to the reaction vessel, and after bubbling with nitrogen, the reaction vessel was heated while nitrogen was flowing in to start reflux. Next, a polymerization initiator solution obtained by diluting 0.1 parts by mass of azobisisobutyronitrile as a polymerization initiator by 10 times with ethyl acetate was put into the reaction vessel, and 100 parts by mass of the total monomer components described in Table 1 were added dropwise over 2 hours. After the dropwise addition, a polymerization initiator solution obtained by diluting 0.1 parts by mass of azobisisobutyronitrile as a polymerization initiator by 10 times with ethyl acetate was again added to the reaction container, and a polymerization reaction was carried out for the time shown in Table 1. 2,2-diphenyl-1-(2,4,6-trinitrophenyl)iminoazonium (DPPH) was added to obtain a solution containing (meth)acrylic acid copolymers A to K. The solvent of the obtained solution was removed to obtain a viscous liquid containing (meth)acrylic acid copolymers A to K with a solid content of 50% to 98%.
[0239] In addition, the weight average molecular weight of (meth)acrylic-type copolymer A-K was measured by the method similar to synthesis example 1 and 2. The result is shown in Table 1.
[0240] In addition, the glass transition temperature of the (meth)acrylic copolymers A to K was obtained by calculating the value obtained by dividing the content ratio of each monomer component constituting each (meth)acrylic copolymer by the glass transition temperature ((content ratio of monomer component (mol %)) / (glass transition temperature of monomer component (K)))), and calculating the reciprocal of the value obtained by summing up the above values of all monomer components constituting the (meth)acrylic copolymer. The results are shown in Table 1.
[0241] [Table 1]
[0242]
[0243] (Examples 1 to 16, Comparative Examples 1 to 3)
[0244] Each material described in Table 2 was added to 150 mL of toluene and mixed to prepare a toluene solution of the resin composition.
[0245] The obtained toluene solution of the resin composition was applied to the release-treated surface of a 50 μm thick PET film (release PET film) subjected to single-sided release treatment using a doctor blade so that the thickness of the dry film was 50 μm, and the applied solution was dried by heating at 110°C for 10 minutes. Next, the release-treated surface of another release PET film was attached to the surface of the resin composition. Then, the temporary fixing material with a double-sided release PET film was obtained by curing at 40°C for 3 days.
[0246] (10% weight loss temperature)
[0247] The release PET films on both sides of the obtained temporary fixing material with a release PET film on both sides were peeled off, and 10 mg was weighed into an aluminum pan. It should be noted that for the temporary fixing material with a release PET film on both sides obtained in Examples 12, 13, and 15, the release PET films on both sides were peeled off and then irradiated for 300 seconds at a wavelength of 365 nm and an irradiation intensity of 70 mW / cm 2 The temporary fixing material or the cured product of the temporary fixing material was cured by ultraviolet light, and 10 mg of the cured product was weighed into an aluminum pan. The aluminum pan was placed in a differential thermal and thermogravimetric simultaneous measuring device (manufactured by Hitachi High-Tech Science, "STA7200"), and heated from 25°C to 500°C at a heating rate of 10°C / min in a nitrogen atmosphere, and the temperature at which the weight of the temporary fixing material or the cured product of the temporary fixing material decreased by 10% was measured. The results are shown in Table 2.
[0248] (Initial adhesion to polyimide at 25°C, adhesion to polyimide at 25°C after heating at 250°C for 2 hours)
[0249] The obtained temporary fixing material with a double-sided release PET film was cut into a width of 1 inch. Next, one release PET film was peeled off from the temporary fixing material with a double-sided release PET film, and laminated on the polyimide film using a laminator to obtain a laminate. The temporary fixing material with a double-sided release PET film obtained in Examples 12 and 13 was laminated on the polyimide film adherend and irradiated from the temporary fixing material side for 300 seconds using an ultra-high pressure mercury lamp with a wavelength of 365 nm and an irradiation intensity of 70 mW / cm 2The temporary fixing material was cured by ultraviolet rays to obtain a laminate. As the polyimide film adherend, a 125 μm thick Upilex (UBE) was adhered to a 1.5 mm thick SUS plate with a double-sided tape, and Leon13DX (LAMI Corporation, speed level 5) was used as the laminator. For the obtained laminate, a peeling test was performed using a tensile tester at 100°C, a tensile angle of 90°, and a tensile speed of 300 mm / min to measure the initial adhesion (N / inch) of the temporary fixing material to the polyimide. As the tensile tester, an angle-free adhesive-film peeling analysis device VPA-2S (Kyowa Interface Science Co., Ltd.) was used. In addition, a 250°C heating plate (ASONE, "ND-3HA") was used to heat the cured temporary fixing material obtained by the same operation for 2 hours, and then the temporary fixing material was measured at 25°C by the same operation. Adhesion to polyimide. The results are shown in Table 2.
[0250] (Gel fraction after curing)
[0251] The temporary fixing materials with double-sided release PET films obtained in Examples 12, 13, and 15 were irradiated for 300 seconds at a wavelength of 365 nm and an irradiation intensity of 70 mW / cm 2 The resin composition was cured by ultraviolet rays, and the cured temporary fixing material was cut into a 50 mm × 100 mm flat rectangle to prepare a test piece. The obtained test piece was immersed in toluene at 23°C for 24 hours, taken out from toluene, and dried at 110°C for 1 hour. The mass of the dried test piece was measured, and the gel fraction was calculated using the following formula. The results are shown in Table 2.
[0252] Gel fraction (mass %) = 100 × (W2-W0) / (W1-W0)
[0253] (W0: mass of substrate, W1: mass of test piece before immersion, W2: mass of test piece after immersion and drying)
[0254] <Evaluation>
[0255] The temporary fixing materials with release PET films obtained in Examples and Comparative Examples were evaluated by the following method.
[0256] (Heat resistance)
[0257] The obtained temporary fixing material with a double-sided release PET film was cut into a circle with a diameter of 200 mm. Next, one release PET film was peeled off from the cut temporary fixing material with a double-sided release PET film, and the polyimide film was attached to a silicon wafer with a diameter of 200 mm and a thickness of 700 μm having a polyimide film on the surface using a vacuum laminator. As the above-mentioned vacuum laminator, ATM-812M (manufactured by Takatori Co., Ltd.) was used. Next, the other release PET film was peeled off, and a glass with a diameter of 200 mm and a thickness of 600 μm (manufactured by Schott Co., Ltd., "Tempax") was attached to the surface opposite to the surface attached to the polyimide film using a vacuum laminator to obtain a laminate. For the temporary fixing material with a double-sided release PET film obtained in Examples 12 and 13, after attaching the glass, an ultra-high pressure mercury lamp was used to irradiate the glass side for 300 seconds at a wavelength of 365 nm and an irradiation intensity of 70 mW / cm 2 The temporary fixing material was cured by ultraviolet rays to obtain a laminate. The obtained laminate was heated for 1 hour using a 250° C. hot plate (manufactured by ASONE, “ND-3HA”).
[0258] The case where there was no peeling was marked as “◎”, the case where the peeling area was less than 5% of the attached area was marked as “○”, and the case where the peeling area was 5% or more of the attached area was marked as “×” to evaluate the heat resistance.
[0259] (Residual glue)
[0260] (Bumpless Wafer)
[0261] The laminate was obtained in the same manner as in the above "(Heat Resistance)". The obtained laminate was heated for 1 hour using a 250°C hot plate (manufactured by ASONE, "ND-3HA"). After natural air cooling, the laminate was irradiated from the glass side to the entire glass surface with a wavelength of 355 nm and an irradiation energy density of 700 mJ / cm 2 The glass was peeled off from the temporary fixing material by a pulsed laser with a frequency of 60 kHz, and then a 180° peeling test was performed using a tensile testing machine (manufactured by Shimadzu Corporation, "AG-IS") at 25°C and a tensile speed of 300 mm / min.
[0262] The residual adhesive was evaluated by recording "◎" when there was no residual adhesive on the surface of the polyimide film of the silicon wafer, "○" when the area of the residual adhesive relative to the bonding area was less than 5%, and "×" when the area of the residual adhesive relative to the bonding area was more than 5%.
[0263] (Wafer with bumps)
[0264] Instead of using a silicon wafer with a diameter of 200 mm and a thickness of 700 μm having a polyimide film on the surface, a wafer with a test pattern having a PBO film on the surface (manufactured by WALTS, "WALTS-TEG FBW100A-0001JY", Cu column height: 35 μm, SnAg height on the Cu column: 15 μm) was used, and a temporary fixing material of a double-sided release PET film was attached to the surface of the wafer having the Cu column. The same operation as in the above "(Heat Resistance)" was performed, to obtain a laminate. The obtained laminate was heated for 1 hour using a 250°C hot plate (manufactured by ASONE, "ND-3HA") . For the laminate after natural air cooling, the entire glass surface was irradiated from the glass side with a wavelength of 355 nm and an irradiation energy density of 700 mJ / cm 2 After the glass was peeled off from the temporary fixing material using a pulsed laser with a frequency of 60 kHz, the temporary fixing material was peeled off from the wafer with the test pattern using a tensile tester (manufactured by Shimadzu Corporation, "AG-IS") at 25°C and a tensile speed of 300 mm / min. The residual adhesive was evaluated by recording "◎" when there was no residual adhesive on the surface of the wafer with the test pattern from which the temporary fixing material was peeled off, recording "○" when the area of the residual adhesive relative to the bonding area was less than 5%, and recording "×" when the area of the residual adhesive relative to the bonding area was more than 5%.
[0265] (Bump deformation and cracks)
[0266] In the above-mentioned evaluation of "(Residual Glue) (Whip with Bumps)", for the surface of the chip with a test pattern from which the temporary fixing material has been peeled off, the case where the rate of occurrence of bump deformation and cracks is less than 1% is recorded as "◎", the case where the rate of occurrence of bump deformation and cracks is greater than 1% and less than 10% is recorded as "○", and the case where the rate of occurrence of bump deformation and cracks is greater than 10% is recorded as "×", and the bump deformation and cracks are evaluated.
[0267] [Table 2]
[0268]
[0269] Industrial Applicability
[0270] According to the present invention, a resin composition can be provided, which can suppress the generation of voids and floating during heat treatment and can be easily peeled off after heat treatment. In addition, according to the present invention, a temporary fixing material comprising the resin composition and a method for manufacturing an electronic component using the temporary fixing material can be provided.
Claims
1. A resin composition, characterized in that Contains a resin having an imide skeleton in a repeating unit of the main chain and a (meth)acrylic copolymer.
2. The resin composition according to claim 1, wherein The (meth)acrylic acid-based copolymer has a structural unit derived from a branched alkyl (meth)acrylate.
3. The resin composition according to claim 2, wherein The (meth)acrylic acid-based copolymer has a content ratio of the structural unit derived from the branched alkyl (meth)acrylate in the (meth)acrylic acid-based copolymer of 20 mol % or more and 80 mol % or less.
4. The resin composition according to claim 1, 2 or 3, wherein The (meth)acrylic copolymer comprises a structural unit derived from an alkyl (meth)acrylate having an alkyl group with 2 to 7 carbon atoms and a structural unit derived from an alkyl (meth)acrylate having an alkyl group with 8 to 8 carbon atoms, wherein the content ratio of the structural unit derived from the alkyl (meth)acrylate having an alkyl group with 2 to 7 carbon atoms in the (meth)acrylic copolymer is 20 mol % to 80 mol %.
5. The resin composition according to claim 1, 2, 3 or 4, wherein The (meth)acrylic copolymer does not have a reactive functional group having a carbon-carbon double bond.
6. The resin composition according to claim 1, 2, 3, 4 or 5, wherein The molecular weight of the (meth)acrylic copolymer is 2,000 or more and 20,000 or less.
7. The resin composition according to claim 1, 2, 3, 4, 5 or 6, wherein The (meth)acrylic copolymer has a glass transition temperature of -70°C to -5°C.
8. The resin composition according to claim 1, 2, 3, 4, 5, 6 or 7, wherein The resin having an imide skeleton in a repeating unit of the main chain includes a resin having no maleimide group and having an imide skeleton in a repeating unit of the main chain.
9. The resin composition according to claim 8, wherein The resin having no maleimide group and having an imide skeleton in a repeating unit of the main chain has an aliphatic group derived from a dimer diamine.
10. The resin composition according to claim 1, 2, 3, 4, 5, 6, 7, 8 or 9, which is thermosetting or photocurable.
11. The resin composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, comprising a compound having a maleimide group.
12. The resin composition according to claim 11, wherein The compound having a maleimide group is a bismaleimide compound or a resin having a maleimide group and having an imide skeleton in a repeating unit of a main chain.
13. The resin composition according to claim 12, comprising a resin having a structural unit represented by the following formula (1) and having a functional group having a maleimide group at at least one position of a terminal and a side chain as the resin having a maleimide group and having an imide skeleton in a repeating unit of the main chain, In formula (1), P 1 represents an aromatic group, Q 1 It represents a substituted or unsubstituted straight-chain, branched or cyclic aliphatic group.
14. The resin composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, further comprising a multifunctional monomer or a multifunctional oligomer, wherein the multifunctional monomer or the multifunctional oligomer has two or more reactive functional groups having carbon-carbon double bonds in the molecule, and the molecular weight of the multifunctional monomer or the multifunctional oligomer is 5000 or less.
15. The resin composition according to claim 14, wherein The content of the (meth)acrylic copolymer is 0.1 parts by mass or more and 20 parts by mass or less based on 100 parts by mass of the total of the resin having an imide skeleton in a repeating unit of the main chain and the polyfunctional monomer or polyfunctional oligomer.
16. The resin composition according to claim 1, 2, 3, 4, 5, 6, 7, 8 or 9, which is non-curable.
17. The resin composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16, wherein The resin composition has a 10% weight reduction temperature of 200° C. or higher.
18. A temporary fixing material comprising the resin composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17.
19. A temporary fixing material comprising an adhesive layer comprising the resin composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17.
20. The temporary fixing material according to claim 19, which is in the form of a tape. 21 . The temporary fixing material according to claim 18 , 19 or 20 , which has an initial adhesive force to polyimide of 0.1 N / inch or more and 1.5 N / inch or less at 25° C.
22. A method for manufacturing an electronic component, comprising: A temporary fixing step of temporarily fixing an electronic component to the temporary fixing material according to claim 18, 19, 20 or 21; a heat treatment step of heat-treating the electronic component; and a peeling step of peeling the electronic component from the temporary fixing material. 23 . The method for manufacturing an electronic component according to claim 22 , further comprising a curing step of curing the temporary fixing material between the temporary fixing step and the heat treatment step.
